(untitled) (Annals of Medical Research, 2023)
Aim: Lateral mass screws are widely used for cervical vertebra fixation. The lateral mass of the C7 vertebra is small in volume. Therefore, the potential risks of biomechanical failure of screws applied to lateral masses make the pedicle screw a better option for the C7 level. Although cervical pedicle screw application is thought to be a difficult and risky procedure in terms of neurovascular injury, it is actually a very safe method since the a.vertebralis does not pass through the C7 vertebra. In this study, we aimed to evaluate the technical details and screw accuracy of free hand pedicle screw placement in C7 vertebra fixation. Materials and Methods: Forty-six patients (92 screws) who underwent free hand pedicle screw placement in the C7 vertebra due to various cervical pathologies were included in this study. Measurements were made on routinely obtained preoperative and postoperative CT images. Screw malpositions and screw application angles, such as the pedicle screw causing a cortical violation in the bone structure or its progression towards the spinal canal and vertebral foramen, were carefully examined. Results: Postoperative CT imaging revealed grade 2a cortical violation in 6 screws, grade 2b cortical violation in 1 screw, and grade 3 malposition in one screw. Radiculopathy was seen postoperatively in one patient. No vascular injury was observed postoperatively in any patients. Conclusion: Placing a free hand pedicle screw in the C7 vertebra is a successful and safe method. At this point, we see the C7 pedicle screw application as a starting point in the learning curve for the entire cervical region pedicle screwing.